2016
DOI: 10.3109/0886022x.2016.1149688
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effects of pentoxifylline on NOS induced by diabetes in rat kidney

Abstract: Objectives Diabetic nephropathy (DN) is the leading cause of end-stage renal disease worldwide. The NO system has been implicated in the pathogenesis of DN. In this study, we aimed to evaluate the healing effect of pentoxifylline on NOS in STZ-induced diabetic rat's kidney. Material and methods In this study, 50 Wistar albino male rats were used. The rats were divided into five groups; Group C control; Group D only diabetes; Group D + PI and D + PII diabetes + pentoxifylline; Group P only pentoxifylline. Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
1
7
0
1
Order By: Relevance
“…[28] showed that 40 mg/kg of PTX reduced inflammatory cell infiltration, hemorrhage, and edema in lung IR injury. Sönmez and Dündar [29] reported that 50 mg/kg of PTX ameliorated eNOS, iNOS, and neuronal NOS protein levels and apoptotic cells in the rat kidney. The beneficial effects of PTX are believed to occur through various mechanisms such as inhibition of PDE, increased cAMP levels and downregulation of tumor necrosis factor‐alpha, IL‐1, IL‐6, IL‐12, transforming growth factor‐β, interferon‐γ, stellate cell activation, and procollagen‐I mRNA expression [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…[28] showed that 40 mg/kg of PTX reduced inflammatory cell infiltration, hemorrhage, and edema in lung IR injury. Sönmez and Dündar [29] reported that 50 mg/kg of PTX ameliorated eNOS, iNOS, and neuronal NOS protein levels and apoptotic cells in the rat kidney. The beneficial effects of PTX are believed to occur through various mechanisms such as inhibition of PDE, increased cAMP levels and downregulation of tumor necrosis factor‐alpha, IL‐1, IL‐6, IL‐12, transforming growth factor‐β, interferon‐γ, stellate cell activation, and procollagen‐I mRNA expression [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…A study in a model of chronic DN for 40 weeks showed that iNOS-derived NO modulates glomerulosclerosis and tubulointerstitial fibrosis in chronic STZ nephropathy [ 66 ]. The drugs for treating DN such as pentoxifylline could exert therapeutic effects by increasing the expression of iNOS protein in the kidneys of a mouse model of STZ-induced DN [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism for relationship between vitamin D and diabetic kidney disease remains unclear however various animal studies have shown that knockout of the vitamin D receptor in diabetic mice is accompanying by severe albuminuria and glomerulosclerosis. Therefore, vitamin D might slow down diabetic kidney disease progression by delaying destruction of b-islet cells, enhancing insulin secretion, and consequently assisting in glucose metabolism (29,30). …”
Section: Vitamin D and Diabetic Nephropathymentioning
confidence: 99%